Essentials for the Canadian medical licensing exam : review and prep for MCCQE, part I - Chowdhury, Sheehan H.; Cozma, Adrian I.; Chowdhury, Jeeshan (Philadelphia : Wolters Kluwer, 2017)
Essentials for the Canadian Medical Licensing Exam reviews key concepts necessary for Canadian medical students and international medical graduates preparing to write the Medical Council of Canada Qualifying Exam (MCCQE), part 1. --
Keywords: Physicians -- Licenses -- Canada -- Examinations -- Study guides; Medicine -- Canada -- Examinations; Physicians -- Licenses -- Canada -- Examinations; Print books